(untitled) (BIRDEM Medical Journal, 2016)
Pregnancy in women with chronic liver disease (CLD) or cirrhosis is rare as CLD usually causes infertility. With improved management of CLD, pregnancy in patients with CLD is likely to become more common. Pregnancy in a CLD patient is likely to be associated with increased fetal and maternal mortality & morbidity. Pregnancy outcome may be influenced by the underlying etiology and extent of liver disease. Here we describe the case of a pregnancy in a young woman with CLD first time detected during pregnancy that ultimately resulted in fetal death, but the mother survived after delivery. Birdem Med J 2015; 5(2): 107-110